The Meaning of Signs in Shadow and Bone Series - Srikandiana, Zulvina Jois; Savitri, Putu Weddha; Maharani, Sang Ayu Isnu (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2025)
This research entitled “The Meaning of Signs in Shadow and Bone Series” and aimed to identify symbols, icon, and indexes in the series. This research also explained how the visual elements help in representing the meaning of the signs. The data in this research were collected from Shadow and Bone series by using documentation method and note-taking technique. This research applied triadic theory by Peirce and visual elements theory by Dyer to analyze the data. The findings of the research revealed that there were 12 visual signs in the series which in a form of 4 symbols, 1 icon, and 7 indexes. Each of the visual signs is correlated with the series story plot. The most dominant visual elements related to the sign meaning was represented by Alina’s character. It can be concluded that Alina is the main character in the series, and the signs reflected Alina’s journey from discriminated until venerated by people. The signs that related to Mal connects him to Alina, which means he is the supporting character for Alina’s journey. In contrast, the signs that related to General Kirigan indicates that he is the antagonist in Alina’s journey and her character development. According to the signs finding, General Kirigan portrayed as the greedy immortal man who addicted to power. He wanted to use Alina’s power for his purpose. He intended to use the shadow fold as a weapon, so that he could expand his sovereign territory and feared by the enemy of Ravka. Keywords: Icon, Index, Signs, Symbol, Visual Elements